ANALISIS KINERJA KEUANGAN DAERAH KABUPATEN OGAN KOMERING ILIR - Fachrizal Bachri (Department of Development Economics, Universitas Sriwijaya, 2011)
The purpose of this study to determine the financial performance of the district of Ogan Komering Ilir. This study uses qualitative descriptive method. The results of this study found that the performance of regional finances based on year-end conditions with the format of compilation has been guided by the Regulation of the Minister of Home Affairs No.13 of 2006 and Government Regulation No. 24 of 2005 on Government Accounting Standards so that the creation of harmonization of drafting structure. Structural harmonization benefit is to analyze the financial performance of this region comparable with the coming years and can be compared with other regencies/cities in South Sumatera province and regencies/cities governments throughout Indonesia. Keywords: Regional Finance, PAD, Balancing Fund.